(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
Autor: Javier Wenceslao Ibañez Jiménez Editorial: Civitas Año de publicación: 2013. 360 págs. ISBN: 9788447045297